The Innovation of Modern Islamic Education System Based on Progressive Boarding School in Madrasah Tsanawiyah Negeri 1 Bima - Su herman; Mahsun Jayadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
The purpose of this research is to find out the implementation of the innovation of modern Islamic education system based on the progressive boarding school in Madrasah Tsanawiyah Negeri 1 Bima which is able to produce a new approach that can accommodate all the development of spiritual, emotional, intellectual and social students. Innovation of modern Islamic education system based on boarding school become an alternative strategy of PAI learning which able to give hope in teaching moral value for learners. This research is a qualitative descriptive, using sociological phenomenology approach.The result of this research shows that the innovation of the Islamic education system in the Madrasah Tsanawiyah Negeri 1 Bima comes from a fundamental thought and contains a meaningful reconstruction of the nation for the realization of the ideals of the developed, equitable, prosperous, dignified, and sovereign state parallel to other nations and countries that have achieved excellence progressing in the spirit, mindset, behavior and always future oriented to realize better conditions as a result of an innovation. Keywords: Innovation in Education, Islamic Education, Boarding School